Franchising in Algeria, Financial Issues (Milan Law Review, 2025)
A key factor in franchising relating to franchisors is the possibility to cash in and repatriate fees and royalties (financial issues). What are the main legal issues relating to financial aspects in Algeria and what is the current practice of the stakeholders in the aspects of financial under the franchise business in Algeria. The main objectives are to examine the legal framework issues relating to financial and to analyse the current practice of the stakeholders in the aspects of financial under the franchise business in Algeria. The doctrinal legal method complemented with qualitative interview was used. The armchair library approach was employed to collect data. The findings show that: the current banking system and legislations relating to the payment of royalties and fees discourage the development of the franchising sector in Algeria. Current franchising practices focus on the financial aspects (payment of royalties and fees) by franchisee who manage the royalty and fees payments by circumventing the law. Franchisee pay royalties without declaring them in Algeria or including them in the sale price of goods imported into Algeria. The results also show that: there is a need to establish a specific law to regulate franchising businesses in Algeria.
Keywords: Franchising; Financial Aspects; Financial Issues; Algeria